Children's Motivation For Learning Guitar In Collective Classes (Orfeu, 2017)
Self-Efficacy Beliefs Theory is one of the possibilities for guiding research about  motivation, since trust in one's own abilities reinforces intrinsic and extrinsic aspects of the motivational process. Thus, the scope of our study was to investigate the motivation of children  learning to play guitar  from the perspective of self-efficacy beliefs in a context of collective teaching. The methodology was a small survey, carried out with seven children 9 - 11 years old, and the data collection was done through a questionnaire with open questions, and questions with response in the likert scale format. Results showed aspects of children's general motivation  regarding group learning, repertoire and public performance, in relation to their self-efficacy beliefs. We observed the presence of vicarious experiences during the classes, and that students valued the possibility of learning from others; successful experiences were poorly perceived by the children; the emotional and physiological state of the children was more controlled in the context of collective performance; verbal persuasion from the teacher had a stronger positive effect on increasing students' self-efficacy beliefs when compared to the persuasion of their peers. Results of this research corroborated with previous studies about learning in a collective context, demonstrating the potential that such a context adds to students’  motivation. In addition, suggestions were offered to the teacher to help maintain the motivation of the students and, consequently, to increase their self-efficacy beliefs.
Keywords: Motivation; Self-efficacy Beliefs; Collective Teaching; Children; Guitar